Impact of exchange rate and foreign exchange gold reserve on prices of gold (International Journal of Innovative Research in Engineering & Management, 2022)
Gold has maintained its existence in Indian  economy since centuries and there is no need for explaining  the importance of this yellow metal in Indian culture as this  valuable commodity always has a significant economic  effect worldwide. This precious metal has marked a land  mark upward trend in terms of prices after phase of recession  in 2008 and early 2009 in global economy. Gold has emerged  as safe haven for investment due to downfall of equity  markets in recent years. Beginning of new millennium has  witnessed a period where prices of this yellow metal started  to climb robustly on a continue basis. Gold has been treated  as hedge against inflation and exchange rate fluctuations. In  the light of above scenario, this paper has analyzed the  impact of exchange rate and foreign exchange reserve on  gold prices.
Keywords: Exchange Rate; Foreign Exchange Reserve; Recession; Inflation